Description of Atherinella brasiliensis (Quoy & Gaimard, 1825) (Atheriniformes: Atherinopsidae) larvae from the Jaguaribe River estuary, Itamaracá island, Northeastern Brazil - França,Elton J. (2007)
The present study describes the external morphology and morphometry of the initial development of Atherinella brasiliensis, and contributes toward broadening knowledge on its biology. A total of 88 larvae and 14 juveniles were used to characterize the morphological development and analyze body proportions. Fish with standard lengths (SL) from 1.4 to 77 mm were used in the study. Larvae hatch at an average of 1.4 mm SL. In the preflexion stage, the larval body is enveloped by a finfold, which begins behind the head. Pectoral fins are the first to be formed and preflexion larvae have four characteristic dendritic chromatophores on the head. The flexion stage begins at an average of 4.4 mm SL; dorsal and anal fins already exhibit pterygiophores and a terminal, somewhat up-turned mouth. At 6.8 mm SL, the flexion stage ends. In the postflexion stage, larvae present greater ossification of the dorsal and anal fin rays, exhibit pelvic fin buds and a darkening of lateral pigmentation. At an average of 8.8 mm SL, head pigmentation intensifies and pelvic fins exhibit conspicuous ossifying rays. Larvae at 11.8 mm SL have all fins formed; the second dorsal fin is the last to be formed at an insertion point posterior to the anal fin. The juvenile period begins at approximately 12 mm SL. At this stage, A. brasiliensis has an anal fin located at the median portion of the body and the posterior end of pectorals surpasses the origin of pelvic fins, which are located at the midpoint between the pectoral and anal fins. Scales are present on the dorsal-lateral region behind the head. The morphological features of A. brasiliensis herein described allow an adequate identification of its larvae and differentiate them from hemiramphid and other atheriniform larvae, thus broadening knowledge on the larval biology of the species.